2002
DOI: 10.1194/jlr.m200010-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Association of GM4 Ganglioside with the Membrane Surrounding Lipid Droplets in Shark Liver

Abstract: By TLC, GM4 was found to be the major ganglioside in the liver of six shark species examined: Odontaspis taurus , Negaprion brevirostris , Sphyrna lewini , Mustelus griseus , Mustelus manazo , and Prionace glauca . A detailed analysis of the glycosphingolipids (GSLs) in the liver of O. taurus (sand tiger shark) showed that it contained approximately 110 nmol of lipid-bound sialic acid per gram of wet tissue, of which 80% was GM4. By extracting the liver of O. taurus with chloroform/methanol, followed by chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…It should be noted that its ceramide contained a hydroxylated fatty acid, which was not observed among the ganglio-series GGs. This specificity of GM4 ceramide has already been reported in human brain [24] and shark liver [25]. GM4 is known to be highly enriched in central nervous system oligodendrocytes that explains its detection in the brain, and in myelin that explains its detection in the optic nerve [8].…”
Section: Resultssupporting
confidence: 63%
“…It should be noted that its ceramide contained a hydroxylated fatty acid, which was not observed among the ganglio-series GGs. This specificity of GM4 ceramide has already been reported in human brain [24] and shark liver [25]. GM4 is known to be highly enriched in central nervous system oligodendrocytes that explains its detection in the brain, and in myelin that explains its detection in the optic nerve [8].…”
Section: Resultssupporting
confidence: 63%
“…GM4 has been reported to be present in other vertebrate sources, such as chicken thymus, chicken embryonic liver, rat kidney, shark liver, and red sea bream intestine [15,16,17,18,19]. A comparative study on GM4 distribution in livers of various vertebrates showed that GM4 was expressed mainly in lower animals, such as bony fish and frog liver [20].…”
Section: Discussionmentioning
confidence: 99%
“…Cer) is the simplest ganglioside. Kuhn and Weigandt first revealed GM4 as a minor ganglioside of human brain [1]. The occurrence of this ganglioside has also been detected in chicken cerebellum, mouse erythrocytes, rat kidney and frog liver.…”
Section: Introductionmentioning
confidence: 95%